A Phase 2 Study to Assess the Immunomodulatory Capacity of a Lecithin-based Delivery System of Curcumin in Endometrial Cancer - Tuyaerts, Sandra; Rombauts, Klara; Everaert, Tina; Van Nuffel, An M. T.; Amant, Frédéric (Frontiers in Nutrition, 2019)
Curcumin is a botanical with anti-tumor and immunomodulatory properties. We hypothesized that curcumin supplementation might influence inflammatory biomarker levels in endometrial carcinoma (EC). In this open-label, non-randomized phase 2 study (NCT02017353), seven EC patients consumed 2 g/day Curcumin Phytosome (CP) orally for two weeks. Blood was taken at baseline, days 1, 7, 14 & 21. The following analytes were measured: curcuminoids and metabolites, 56 inflammatory biomarkers, COX-2, frequencies of myeloid-derived suppressor cells, dendritic cells and NK cells, expression of MHC molecules on leukocytes and monocytes and activation/memory status of T cells. Patients completed quality of life (QoL) questionnaires at baseline and end of treatment. Curcumin metabolites were detectable in plasma upon CP intake. CP downregulated MHC expression levels on leukocytes (P=0.0313), the frequency of monocytes (P=0.0114) and ICOS expression by CD8+ T cells (P=0.0002). However, CP upregulated CD69 levels on CD16- NK cells (P=0.0313). No differences were observed regarding inflammatory biomarkers, frequencies of other immune cell types, T cell activation and COX-2 expression. A non-significant trend to improved QoL was observed. Overall, CP-induced immunomodulatory effects in EC were modest without significant QoL changes. Given the small population and the observed variability in inter-patient biomarker levels, more research is necessary to explore whether benefits of CP can be obtained in EC by different supplementation regimens. Trial registration: ClinicalTrials.gov: NCT02017353; European Clinical Trials Database (EudraCT): 2013-001737-40.